2011
DOI: 10.1099/vir.0.033134-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile and subcellular localization of Torque teno sus virus proteins

Abstract: In the present study, the expression, generation and subcellular localization of Torque teno sus virus (TTSuV) proteins were characterized into two genetically distinct TTSuV species (TTSuV1 and TTSuV2). Following transfection of three TTSuV1 and TTSuV2 full-length ORF (ORF1, ORF2 and ORF3) expression constructs into porcine kidney cells, alternative splice variants encoding new TTSuV protein isoforms were identified for the first time. Proteins encoded from ORF1 and ORF3 were localized in the nucleoli of porc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 38 publications
4
20
0
1
Order By: Relevance
“…5), putative mRNA1, encoding full-length ORF1 of TTSuV2, was not detected (data not shown), which may suggest a smaller quantity and lower integrity of mRNA1 than of mRNA2 and mRNA3. In accordance with the result described by Martinez-Guinó et al, splicing of the 91-nt intron 2 sequence into mRNA3 also occurred posttranscription of the TTSuV2 ORF1-GFP fusion gene based on a non-fulllength viral clone (27).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…5), putative mRNA1, encoding full-length ORF1 of TTSuV2, was not detected (data not shown), which may suggest a smaller quantity and lower integrity of mRNA1 than of mRNA2 and mRNA3. In accordance with the result described by Martinez-Guinó et al, splicing of the 91-nt intron 2 sequence into mRNA3 also occurred posttranscription of the TTSuV2 ORF1-GFP fusion gene based on a non-fulllength viral clone (27).…”
Section: Discussionsupporting
confidence: 73%
“…The TTSuV2 ORF1 protein was expressed in cell nuclei, especially in nucleoli, which is consistent with the localization of human TTV ORF1 in Huh-7 cells transfected with the circular full-length TTV genomic DNA by immunoblotting with the ORF1-specific antibody (30). Most recently, it was also reported that TTSuV1 or TTSuV2 ORF1-GFP fusion protein expressed from the recombinant construct accumulated in the nucleoli of PK-15 cells (27).…”
Section: Discussionsupporting
confidence: 55%
“…The predominant transcripts detected in vitro and in vivo of ORF1 are spliced and full-length ORF1 transcripts have not been detected [5,6]. Splicing of TTSuVk2a ORF1 results in three protein isoforms (ORF1-A, -B and -C) and the amino acid composition between them varies, depending on the splicing site used [5,6].…”
Section: Introductionmentioning
confidence: 92%
“…ORF3 can only be translated after splicing of the mRNA precursor, and splicing of the ORF1 mRNA transcript results in different protein isoforms [5,6], as is also indicated in human TTV [7,8]. The predominant transcripts detected in vitro and in vivo of ORF1 are spliced and full-length ORF1 transcripts have not been detected [5,6]. Splicing of TTSuVk2a ORF1 results in three protein isoforms (ORF1-A, -B and -C) and the amino acid composition between them varies, depending on the splicing site used [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Committee on Taxonomy of Viruses (ICTV), the viral family comprises 11 genera, including human and animal anelloviruses. Anelloviruses are species specific, characterized by a high degree of genetic divergence, and similar genome organization and gene expression strategy (Martínez-Guinó et al, 2011;Okamoto et al, 2001).…”
Section: Introductionmentioning
confidence: 99%